Predictive symptoms and comorbidities for severe COVID-19 and intensive care unit admission: a systematic review and meta-analysis - Jain, Vageesh; Yuan, Jin-Min (International journal of public health, 2020)
Objectives COVID-19 has a varied clinical presentation. Elderly patients with comorbidities are more vulnerable to severe disease. This study identifies specific symptoms and comorbidities predicting severe COVID-19 and intensive care unit (ICU) admission. Methods A literature search identified studies indexed in MEDLINE, EMBASE and Global Health before 5th March 2020. Two reviewers independently screened the literature and extracted data. Quality appraisal was performed using STROBE criteria. Random effects meta-analysis identified symptoms and comorbidities associated with severe COVID-19 or ICU admission. Results Seven studies (including 1813 COVID-19 patients) were included. ICU patients were older (62.4 years) than non-ICU (46 years), with a greater proportion of males. Dyspnoea was the only symptom predictive for severe disease (pOR 3.70, 95% CI 1.83–7.46) and ICU admission (pOR 6.55, 95% CI 4.28–10.0). COPD was the strongest predictive comorbidity for severe disease (pOR 6.42, 95% CI 2.44–16.9) and ICU admission (pOR 17.8, 95% CI 6.56–48.2), followed by cardiovascular disease and hypertension. Conclusions Dyspnoea was the only symptom predictive for severe COVID-19 and ICU admission. Patients with COPD, cardiovascular disease and hypertension were at higher risk of severe illness and ICU admission.